2015
DOI: 10.1007/s10126-015-9634-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity of Sponge-Associated Fungi from the Caribbean and the Pacific of Panama and Their In Vitro Effect on Angiotensin and Endothelin Receptors

Abstract: Fungi occupy an important ecological niche in the marine environment, and marine fungi possess an immense biotechnological potential. This study documents the fungal diversity associated with 39 species of sponges and determines their potential to produce secondary metabolites capable of interacting with mammalian G-protein-coupled receptors involved in blood pressure regulation. Total genomic DNA was extracted from 563 representative fungal strains obtained from marine sponges collected by SCUBA from the Cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…During Expedition 337, cell concentrations of prokaryotes (<10 4 cells cm −3 ) in the deep coal‐bearing sediments below ∼1.5 kmbsf were notably lower than those predicted by the global regression line, suggesting that the drilling operation has approached the lower boundary of the deep subseafloor biosphere at this site (Inagaki et al ., ). Based on alignment and similarity analysis of the ITS and 28S rRNA gene sequences of 69 fungal isolates representing 27 species in this study, we found that almost all the reference sequences in the database are derived from plants, soil, and fresh water in the terrestrial environments with the similarity of >97% (Table ), except Eutypalla scoparia with high similarity to the reference sequences detected from a marine sponge (Bolaños et al ., ). This result suggests that the fungi we isolated from the deep sediment samples are phylogenetically close to known terrestrial fungi that they were there to begin with, i.e., when sediments were deposited in the Oligocene and Miocene.…”
Section: Discussionmentioning
confidence: 97%
“…During Expedition 337, cell concentrations of prokaryotes (<10 4 cells cm −3 ) in the deep coal‐bearing sediments below ∼1.5 kmbsf were notably lower than those predicted by the global regression line, suggesting that the drilling operation has approached the lower boundary of the deep subseafloor biosphere at this site (Inagaki et al ., ). Based on alignment and similarity analysis of the ITS and 28S rRNA gene sequences of 69 fungal isolates representing 27 species in this study, we found that almost all the reference sequences in the database are derived from plants, soil, and fresh water in the terrestrial environments with the similarity of >97% (Table ), except Eutypalla scoparia with high similarity to the reference sequences detected from a marine sponge (Bolaños et al ., ). This result suggests that the fungi we isolated from the deep sediment samples are phylogenetically close to known terrestrial fungi that they were there to begin with, i.e., when sediments were deposited in the Oligocene and Miocene.…”
Section: Discussionmentioning
confidence: 97%
“…This is corroborated by data for Cinachyrella alloclada from the Caribbean that showed that the cosmopolitan Phoma sp. (Ascomycota) is the dominant sponge-associated fungus, while nine more ascomycete species were found [5]. Indeed, in the reconstructed LAGLIDADG protein phylogeny (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only Höller et al (2000) isolated Mucor, a zygomycete. Furthermore, Flemer (2013) and Bolaños et al (2015) recovered ascomycetes in subtidal sponges under the genus Axinella while no ascomycetes were isolated from mangrove sponge Axinella sp. collected in Aklan, Philippines.…”
Section: Environment-dependent Fungal Diversitymentioning
confidence: 99%
“…Fungi have been isolated from subtidal sponges in tropical, subtropical and temperate countries. Wang et al 2008;Caballero-George et al 2010;Paz et al 2010;Zhou et al 2011;Thirunavukkarasu et al 2012;Flemer 2013;Henriquez et al 2013;Bolaños et al 2015). In Asia, there have been published information on the diversity of sponge-associated fungi in countries like China (Zhang et al 2009;Liu et al 2010;Ding et al 2011;Zhou et al 2011;Yu et al 2012;He et al 2014;Jin et al 2014), India (Meenupriya and Thangaraj 2010;Thirunavukkarasu et al 2012) Indonesia (Namikoshi et al 2002), Israel , Malaysia (Mahyudin 2008) and Russia ).…”
Section: Introductionmentioning
confidence: 99%